(untitled) (Studia theodisca, 2019)
In his translation of Antigone Hölderlin certainly used the ancient scholia, which he read at the margins of the edition he had available (the so called Brubachiana, Frankfurt 1544), or in another source (perhaps the commentary on the Theban plays of Sophocles by Joachim Camerarius, 1534). This paper analyzes the beginning of Hölderlin’s translation (vv. 1-11) in a close reading focused on its relationship with the Greek text and its tradition; special attention will be paid to the poetic significance of Hölderlin’s lexical choices. The aim is to demonstrate the inner poetic coherence of Hölderlin’s translation and, as a consequence, to hint at the consistency of his interpretation of Sophocles’ Antigone.